Determination of cyanogenic compound amygdalin and prunasin in almond kernels (prunus dulcis l) by using liquid chromatography (2013)
In the present work we applied a technics to determine and also permit quantification for separating the cyanogenic components that could be present in the mature almond seed (Prunus dulcis). Among the methods selected the chromatography of liquids of high resolution (HPLC), that permit the quantification of the glycosides for the separation process of lyophilization where there is less  surface there is more contact to sublimation with the degreased samples, looking at the obtain results and suppoted by other investigations, the use of 100 % methanol extract as a mobile phase acetonitrile-water (80:20) the results obtained of the glycosides cyanogenics resulting in a concentration of maximum amygdalin aparting the time of extraction of twelve hours, amygdalin is obtained, with a concentration of 9.8 mg / 100 g of dry sample. The chromatograms obtained a time of retention (Tr), amygdalin 3,4 and prunasin 5,7 two peaks with excellent resolution, to the above conditions can be used for analysis by HPLC, identification and quantification of amygdalin and prunasina.